Radio Frequency Identification (RFID) tag antenna design at Ultra High Frequency (UHF) band - Seok, Yew Been; Hoon, Wee Fwen; Mohamed Fareq, Abdul Malek; Seng, Lee Yeng; Siti Zuraidah, Ibrahim (2017)
This project is to design a Radio Frequency Identification (RFID) high sensitivity tag antenna which operates at UHF frequency band in Malaysia between 919 MHz to 923 MHz. RFID is a type of wireless and radio wave technology that allows for a small RFID chip to be embedded in certain physical object and uniquely identified by an RFID reader. The major contempilation is that the tag antennas will have longer read ranges but in small sizes. While reducing the size of these antennas cause gain decrease will cause reduction in the read range. Another challenge in designing passive RFID tags antennas is to have the highest impedance matching to achieve high efficiency and low effects of the electromagnetic environment. This project was providing two methods to overcome those problems. Firstly, construct meander line structure to reduce the antenna size and design proposed tag antenna with T-match circuit to achieve conjugate matching with the application-specific integrated circuit so that the reading range of the RFID tag is greatly enhanced. On the other hand, the result show the tag directivity and gain was meets the RFID tag design requirements. This project is useful to be implemented in the RFID industry based on today’s technology.